Exploring factors affecting adherence to multiple micronutrient supplementation during pregnancy in Cambodia: A qualitative analysis - Jocelyne M. Labonté; Mai‐Anh Hoang; Aishwarya Panicker; Hou Kroeun; Meng Sokchea; Sreang Sambo; Vin Sokhal; Cassandra Sauer; Mary Chea; Crystal D. Karakochuk (Maternal and Child Nutrition)
Abstract For decades, iron‐folic acid (IFA) supplements have been provided to pregnant women in Cambodia through antenatal care (ANC) services. However, mounting evidence suggests that multiple micronutrient supplements (MMS) are superior to IFA supplements in achieving positive pregnancy outcomes. The possibility of transitioning from IFA supplements to MMS in government‐run health centres is currently being assessed in Cambodia. A crucial component of this assessment involves identifying factors that can influence adherence to MMS, as low adherence can reduce supplement effectiveness. Consequently, this study aimed to explore the potential barriers and enablers to MMS adherence and identify the strengths and challenges of current ANC services. Data were collected through nine focus group discussions with pregnant women (n = 19), family members (n = 18) and midwives (n = 18) and three in‐depth interviews with maternal and child health chiefs (n = 3) in Cambodia and analysed via content analysis. Factors found to influence MMS adherence included attitudes, perceptions and beliefs about MMS; knowledge related to supplementation; ANC counselling; family influence; physical health; access to ANC; supply of MMS; and supplementation norms. Noted strengths of ANC services were the quality of ANC materials, tailored patient education, midwife–patient relationships and flexibility of provided services. Primary challenges related to poor availability of ANC materials, inadequate midwife training, heavy workload, limited funding and suboptimal physical spaces for delivering ANC services. To effectively promote MMS adherence, strategies must involve pregnant women, family members and community leaders; seek to address knowledge gaps and misconceptions related to MMS; and enhance the availability and accessibility of ANC services.